Corticopontocerebellar Connectivity Disruption in Congenital Hemiplegia. (October 2015) - Fiori, Simona; Pannek, Kerstin; Pasquariello, Rosa; Ware, Robert S.; Cioni, Giovanni; Rose, Stephen E.; Boyd, Roslyn N.; Guzzetta, Andrea
Background . Crossed cerebellar diaschisis is the disruption of functional connectivity between cerebrum and cerebellum after hemispheric unilateral brain lesions. In adults and to a lesser extent in children, crossed cerebellar diaschisis has been largely investigated by functional connectivity and demonstrated to influence paretic hand function. Objective . We aim to demonstrate a disruption in structural corticopontocerebellar (CPC) connectivity in children with congenital brain lesions and examine its correlation with paretic hand motor function. Methods . Thirty-six children (Manual Ability Classification System: I, n = 21; II, n = 15) with unilateral brain lesions and 18 controls were analyzed in a case-control study, and diffusion magnetic resonance imaging data were acquired at 3T. High angular resolution diffusion imaging probabilistic tractography was employed for the region of interest–based reconstruction of CPC tracts. To identify statistical differences in structural cerebrocerebellar connectivity between case and control groups, an asymmetry index based on the number of streamlines of CPC tracts was used. In the case group, the correlation between asymmetry index and hand function measures was also determined. Results . Projections through the middle cerebellar peduncle to the contralateral cerebral cortex showed greater asymmetry in children with congenital unilateral brain lesion compared to controls ( P = .03), thus indicating a disruption of structural cerebrocerebellar connectivity. The degree of asymmetry index showed a correlation ( P < .03; r = −0.31) with impaired hand abilities in bimanual tasks. Conclusions . Disruption of structural cerebrocerebellar connectivity is present in patients with congenital unilateral brain injury and might be related to impaired hand function in bimanual skills, with potential implication in tailoring early intervention strategies.